Sustainable Landscape Management Strategies for Urban Parks: Lessons from Pakui Sayang Park, Makassar - Nurfaida Nurfaida; Nur Syahraeni; Novaty Eny Dungga; Tigin Dariati; Muhammad Faried (School of Postgraduate Studies, Diponegoro Univer, 2026)
Urban parks play a critical role in supporting ecological balance, enhancing public well-being, and fostering inclusive spaces within rapidly developing cities. This study aims to formulate a sustainable landscape management strategy for Pakui Sayang Park in Makassar, Indonesia, by integrating physical, ecological, managerial, and social considerations. Utilizing a qualitative descriptive approach supported by a SWOT (Strengths, Weaknesses, Opportunities, Threats) framework, the research assesses the park’s infrastructure, maintenance routines, labor effectiveness, and inclusive features through field observation, stakeholder interviews, and secondary data analysis. Results indicate significant management challenges, including limited workforce, underfunding, inadequate facility maintenance, and barriers to accessibility for vulnerable groups. Despite these issues, the park’s strategic location, ecological diversity, and community engagement present considerable opportunities for improvement. The SWOT analysis places the park in the Strength-Opportunity quadrant, suggesting that optimizing existing resources and leveraging external advantages can guide effective interventions. Key strategies include improving maintenance routines, enhancing managerial supervision, and promoting inclusivity through infrastructure upgrades. This research underscores the importance of integrated management that aligns ecological, social, and economic dimensions, offering a replicable model for sustainable urban park governance in comparable metropolitan contexts.